1997
DOI: 10.1016/s0014-5793(97)00035-5
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal protection of LDL and HDL oxidised by OH free radicals in the presence of oxygen

Abstract: The aim of this work was to compare the behaviour of HDL oxidised by "OH or 'OH/0' 2~ free radicals produced by gamma radiolysis in the absence or in the presence of LDL at the same concentration of 3 g-1 -1 , in order to specify the possibility of reciprocal protection of HDL and LDL towards lipid peroxidation. This oxidation was quantitatively evaluated by the decrease of endogenous a-tocopherol and the formation of oxidation products (thiobarbituric acid-reactive substances and conjugated dienes) and by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Thus, Tribble et al . Similarly, we obtained evidence that HDL could be protected by LDL against radical-induced oxidation in the presence of oxygen (action of • OH/O 2 •free radicals generated by γ-radiolysis) (56). These authors showed that HDL inhibited both Cu 2+ and Fe 3+ -induced peroxidation of LDL-associated lipids, which was consistent with a direct antioxidant effect of HDL.…”
Section: Protective Role Of Native Hdl Towards Ldl Oxidationsupporting
confidence: 73%
See 2 more Smart Citations
“…Thus, Tribble et al . Similarly, we obtained evidence that HDL could be protected by LDL against radical-induced oxidation in the presence of oxygen (action of • OH/O 2 •free radicals generated by γ-radiolysis) (56). These authors showed that HDL inhibited both Cu 2+ and Fe 3+ -induced peroxidation of LDL-associated lipids, which was consistent with a direct antioxidant effect of HDL.…”
Section: Protective Role Of Native Hdl Towards Ldl Oxidationsupporting
confidence: 73%
“…Indeed, others (55,56) suggested the existence of a reciprocal protection of HDL and LDL, which should involve other mechanisms. Indeed, others (55,56) suggested the existence of a reciprocal protection of HDL and LDL, which should involve other mechanisms.…”
Section: Protective Role Of Native Hdl Towards Ldl Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Human HDL are well known for their protective effect against the development of the atherosclerotic process, because of their ability to promote cholesterol efflux from cells [11, 12, 46]and to inhibit oxidative modification of LDL [2, 38, 47, 48]. However, compared to LDL, less is known about the peroxidation of HDL and their susceptibility to oxidation in different pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, these results strongly suggest that the number of targets on HDL decreases with aging. In the oxidative theory of atherosclerosis based on the reciprocal protection of LDL and HDL [47], reduction in the number of potentially oxidizable targets on the HDL may direct radical attacks onto LDL, thus contributing indirectly to LDL oxidation and in turn to the enhancement of the incidence of cardiovascular diseases with aging.…”
Section: Discussionmentioning
confidence: 99%